Coherent campaigns? Campaign broadcast and social messaging. Issue 5 (12th September 2016) - Bode, Leticia; Lassen, David S.; Kim, Young Mie; Shah, Dhavan V.; Fowler, Erika Franklin; Ridout, Travis; Franz, Michael
Abstract : Purpose: Despite the growing use of social media by politicians, especially during election campaigns, research on the integration of these media into broader campaign communication strategies remains rare. The purpose of this paper is to ask what the consequences of the transition to social media may be, specifically considering how Senate candidates' use of a popular social network, Twitter, is related to their messaging via broadcast media in the form of campaign advertising, in terms of content and tone. Design/methodology/approach: To address this research question, a unique data set combining every tweet (10, 303) and every television ad aired (576, 933 ad airings) by candidate campaigns for the US Senate during the 2010 campaign is created. Using these data, tweets and ads are analyzed for their references to issues as well as their overall tone. Findings: Findings demonstrate that social messaging often resembles broadcast advertising, but that Twitter nonetheless occupies a unique place in modern campaigns in that its tone tends to be quite different than that of advertisements. Research limitations/implications: This sheds light on a larger debate about whether online campaigning has produced a fundamental change in election practices or whether new media simply extend "campaigning as usual." Originality/value: This study uses a novel data set, encompassing the complete universe of ads and tweets distributed by candidates for Senate in 2010.